External Factors Associated With Food Waste In Patients With Diabetes Mellitus At RSUD Undata Palu Central Sulawesi Province - Sance Angreani Agustina Tombokan; Nensy Florence Damanik; Adillah Imansari (Sean Institute, 2024)
The successful implementation of food delivery in hospitals is closely related to the presence of food waste which indicates less than optimal food delivery so that the nutritional needs of patients are not met. Obtained data on food waste in diabetes mellitus patients at RSUD Undata is high as much as 50.9%. The purpose of this study was to analyze external factors associated with the occurrence of food waste in patients with diabetes mellitus at RSUD Undata Palu Central Sulawesi Province. This type of research is quantitative with an analytic observation approach using a cross-sectional design. The sample in this study were all patients with a diagnosis of diabetes mellitus who were treated in the Inpatient Room of RSUD Undata totaling 30 people, who were taken by purposive sampling, with primary and secondary data collection techniques. Data analysis using univariate and bivariate techniques. Food acceptability (aroma, taste, texture, color combination) of patients with diabetes mellitus on food waste obtained P> 0.05, as well as waiter's attitude towards food obtained P> 0.05 and standard portion of food on food waste obtained P> 0.05. there is no significant relationship between external factors and the occurrence of food waste in patients with diabetes mellitus at RSUD Undata Palu Central Sulawesi Province. it is necessary to be careful with diabetes mellitus patients who bring food from outside the hospital, because this affects the remaining food of diabetes mellitus patients.